2015
DOI: 10.17240/aibuefd.2015.15.1-5000128608
|View full text |Cite
|
Sign up to set email alerts
|

5e Öğrenme Modeline Göre Düzenlenmiş Eğitim Durumlarının Akademik Başarı Ve Tutuma Etkisi

Abstract: Bu çalışmada, 5E Öğrenme Modeli'ne göre düzenlenmiş dördüncü sınıf Fen ve Teknoloji dersi eğitim durumlarının öğrencilerin öğrenme düzeyi ve tutuma etkisinin belirlenmesi amaçlanmıştır. Araştırmada, kontrol gruplu ön test-son test deneysel desen kullanılmıştır. Son testten üç ay sonra da kalıcılık-kararlılık testleri uygulanmıştır. Çalışma, Ankara Özel Tevfik Fikret İlköğretim Okulu'nda 4. Sınıf Fen ve Teknoloji dersi kapsamında yürütülmüştür. Denel işlem 18 hafta sürmüştür. 2011-2012 öğretim yılında bu dersi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
1
5
0
6
Order By: Relevance
“…In the studies conducted in terms of affective objectives related to the affective field, it was found that web 2.0 tools increased the motivation of the students (Baş, and Tüzün, 2007) and increased the student's attitude towards the course (Katwibun, 2014;Özerbaş, 2012), computer-based education has developed a positive attitude towards the course according to the traditional method (Özabacı and Olgun, 2011;Yenice, 2003) and poses positive changes in students' perceptions (Mevarech and Rich, 1985), web 2.0 applications, as well as motivation, self-confidence has been raised (Kurtuluş, Ada and Burn, 2014) was put forward. Research shows that the use of technology in the educational environment enables students to develop positive attitudes towards the lesson by attracting their attention and motivation, giving importance to the lesson and realizing the affective objectives of the course.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies conducted in terms of affective objectives related to the affective field, it was found that web 2.0 tools increased the motivation of the students (Baş, and Tüzün, 2007) and increased the student's attitude towards the course (Katwibun, 2014;Özerbaş, 2012), computer-based education has developed a positive attitude towards the course according to the traditional method (Özabacı and Olgun, 2011;Yenice, 2003) and poses positive changes in students' perceptions (Mevarech and Rich, 1985), web 2.0 applications, as well as motivation, self-confidence has been raised (Kurtuluş, Ada and Burn, 2014) was put forward. Research shows that the use of technology in the educational environment enables students to develop positive attitudes towards the lesson by attracting their attention and motivation, giving importance to the lesson and realizing the affective objectives of the course.…”
Section: Resultsmentioning
confidence: 99%
“…Alanyazın incelendiğinde duyuşsal alan hedefleri üzerinde teknoloji etkililiği ile ilgili araştırmalar sınırlı olmakla birlikte, eğitimde kullanılan teknolojilerin öğrencilerin duyuşsal alan hedeflerini de etkilediği, bu sayede öğrenci başarıları üzerinde olumlu katkılar sağladığı sonucuna ulaşılan çalışmalar bulunmaktadır. Yapılan çalışmalarda akıllı tahtanın motivasyonu ve derse olan ilgiyi arttırdığı için öğrencilerin bilgi ve becerilerini arttırdığı (Yıldızhan, 2013), akıllı tahta uygulamalarının derse yönelik tutum ve motivasyonlarda yükselmeyi sağladığı (Erdem ve Kara, 2016), Web 2.0 araçlarının öğrencinin dersle ilgili motivasyonun, ilginin ve dersin değerine ilişkin anlayışın artmasını sağladığı (Baş, ve Tüzün, 2007;Ramma, Bholoa, Watts ve Nadal, 2017), öğrencinin derse yönelik tutumunu arttırdığı (Katwibun, 2014;Özerbaş, 2012), öğrenmeye ilgisini www.turkishstudies.net/education ve tutumunu önemli ölçüde geliştirdiği (Hwang ve Chang, 2016), Web 2.0 uygulamalarının motivasyonun yanı sıra özgüveni de arttırdığı (Kurtuluş, Ada ve Yanık, 2014) ortaya konulmuştur.…”
Section: Tartışma Ve Sonuçunclassified
“…The basis of constructivist approach is suggesting that people should construct their knowledge by themselves rather than receiving them directly from others (Ayvacı & Bakırcı, 2012). According to Moussiaux & Norman (2003), constructivism is based on an idea of constructing personal and individual knowledge rather than reproducing others' knowledge (Bıyıklı & Yagcı, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Creative drama, as a method, provides developing various characteristics of individuals, and has been applied increasingly for the academic achievement of students in terms of different courses (Kırmızı, 2012;Şahin, 2012;Rüzgâr, 2014;Bıyıklı & Yağcı, 2015;Bingöl, 2015;Bulut & Aktepe, 2015;Dikmenli-Vardar, 2015;Ulubey & Gözütok, 2015;Yıldırım & Işık, 2015), and also to transform students' attitudes to be positive towards courses. Attitude is a concept which has been studied for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Bireylerin çeşitli özelliklerinin gelişmesini sağlayan yaratıcı drama yöntemi, öğrencilerin farklı öğretim kademelerindeki derslerde akademik başarılarının arttırılmasına (Kırmızı, 2012;Şahin, 2012;Rüzgâr, 2014;Bıyıklı & Yağcı, 2015;Bingöl, 2015;Bulut & Aktepe, 2015;Dikmenli-Vardar, 2015;Ulubey & Gözütok, 2015;Yıldırım & Işık, 2015) ve derse yönelik tutumlarının olumluya dönüştürülmesine yönelik kullanılmıştır.…”
Section: Introductionunclassified